MONEY POLITICS AS AN OBSTACLE TO THE LEADERSHIP CADRE OF THE LEGISLATIVE ELECTION STUDY IN THE 2024 ELECTION IN SUBUR ASAHAN VILLAGE: Politik Uang sebagai Penghambat Perkaderan Kepemimpinan Studi Pemilihan Legislatif pada Pemilu Tahun 2024 di Desa Subur Asahan - Rizki, Fachri; Harahap, Syahrin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Money politics often uses people's poverty as a shortcut to gain power. The purpose of this research is to identify and analyze the practice of money politics in general elections, especially legislative elections, which have an impact on leadership cadres in villages, especially subur villages. This research, which uses an Islamic sociopolitical approach, aims to connect the phenomenon of money politics practices based on social interests with the foundation of Islamic values. The data analysis method used in this study is qualitative data analysis, aiming for organizing, recording data records from the field and to answer research questions and gain a deep understanding of the topics discussed. Data collection techniques include observation and in-depth interviews with community leaders and the community itself. The results and discussions show that money politics hinders leadership development in Subur Village. This is evidenced by the widespread practice of money politics during elections, which no longer serves as a rational platform to choose candidates, but rather as a transactional platform. This creates inequality among legislative candidates or leaders, as it favors candidates who have financial power. This also results in competent candidates not being elected and promoting underprivileged leaders.